2017
DOI: 10.1128/aac.02505-16
|View full text |Cite
|
Sign up to set email alerts
|

Ga(III) Nanoparticles Inhibit Growth of both Mycobacterium tuberculosis and HIV and Release of Interleukin-6 (IL-6) and IL-8 in Coinfected Macrophages

Abstract: Treatment of individuals coinfected with human immunodeficiency virus (HIV) type 1 and Mycobacterium tuberculosis is challenging due to the prolonged treatment requirements, drug toxicity, and emergence of drug resistance. Mononuclear phagocytes (MP; macrophages) are one of the natural reservoirs for both HIV and M. tuberculosis. Here, the treatment of HIV and M. tuberculosis coinfection was studied by preloading human macrophages with MP-targeted gallium (Ga) nanoparticles to limit subsequent simultaneous inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…44 GaNP is known to facilitate phagosome maturation, inhibit growth of M.tb in macrophages, inhibit HIV infection through release of interferons and can be targeted to human macrophages infected with both M.tb and HIV. 45,46 These studies support our results and point to the possibility that GaNP would be an effective intervention against bacterial biofilms. It has not escaped our attention that cyclosporine-A as an adjunct to existing anti-tubercular drugs could be a potential strategy to address the problem of eradicating latent TB by first activating the bacterium, by virtue of its immune-suppressive action, followed by the biofilm inhibition reported in our study.
Fig.
…”
Section: Discussionsupporting
confidence: 81%
“…44 GaNP is known to facilitate phagosome maturation, inhibit growth of M.tb in macrophages, inhibit HIV infection through release of interferons and can be targeted to human macrophages infected with both M.tb and HIV. 45,46 These studies support our results and point to the possibility that GaNP would be an effective intervention against bacterial biofilms. It has not escaped our attention that cyclosporine-A as an adjunct to existing anti-tubercular drugs could be a potential strategy to address the problem of eradicating latent TB by first activating the bacterium, by virtue of its immune-suppressive action, followed by the biofilm inhibition reported in our study.
Fig.
…”
Section: Discussionsupporting
confidence: 81%
“…Our previous works demonstrated that macrophage-targeted Ga(III) nanoparticles have a prolonged antimicrobial effect against Mycobacterium abscessus, Mycobacterium avium, Mycobacterium tuberculosis, and Mycobacterium smegmatis within macrophages because of sustained Ga(III) release over time (27)(28)(29)39). In the current work, we found that THP-1 cells preloaded with GaMP, CDGaPP, or eFGaMP exhibited resistance to P. aeruginosa infection, but only for 3 days, losing all activity at day 5 postloading.…”
Section: Discussionmentioning
confidence: 47%
“…The glyoxalase pathway is a promising drug target for neurodegenerative diseases. Drug discovery [4] , [140] , [141] , [142] , [143] , [144] and delivery [145] , [146] , [147] processes could be explored in this target against neurodegenerative diseases. Novel flavonoids could be designed, synthesized, and tested to protect neurodegenerative diseases through glyoxalase pathway.…”
Section: Discussionmentioning
confidence: 99%